Mangupura sebagai Ibu Kota Kabupaten Badung: Suatu Penelusuran Historis dan Pengembangan Wilayah - I Putu Gede Suwitha, (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
This study analysis the new capital city of Badung afterDenpasar was decided to be the capital city of the governmentof Denpasar. Where should the location of the new capitalcity of Badung ? and what is the name of the city? The citymust fulfil the condition of a new capital city according to thetheoretical frame works that exist so far. This city should alsobe in cooperation with the former city of Denpasar which hasalready become metropolitan city.This research was done using historical method. The datacollection was done through library research and field workin analyzing the problems. Theories and concepts about citieswere used.
Keywords: Badung; Mangupura; urbanization; city state; residence; non agraries